Accelerated Solutions for Transcendental Stiffness Matrix Eigenproblems - F.W. Williams; D. Kennedy (Shock and Vibration, 1996)
This article outlines many existing and forthcoming methods that can be used alone, or in various combinations, to accelerate the solutions of the transcendental stiffness matrix eigenproblems that arise when the stiffness matrix is assembled from exact member stiffnesses, which are obtained by solving the member differential equations exactly. Thus distributed member mass and/or the flexural effect of axial loading are incorporated exactly, and the solutions are the natural frequencies for vibration problems or the critical load factors for buckling problems.